Solasodine, Isolated from Solanum sisymbriifolium Fruits, Has a Potent Anti-Tumor Activity Against Pancreatic Cancer - Fan Y; Li Z; Wu L; Lin F; Shao J; Ma X; Yao Y; Zhuang W; Wang Y (Dove Medical Press, 2021)
Yingchao Fan,* Zhumeng Li,* Liting Wu, Feng Lin, Jinfeng Shao, Xiaoyan Ma, Yonghua Yao, Wenfang Zhuang, Yuan Wang Medical Laboratory, Shidong Hospital Affiliated to University of Shanghai for Science and Technology, Shanghai, 200438, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wenfang Zhuang; Yuan WangMedical Laboratory, Shidong Hospital Affiliated to University of Shanghai for Science and Technology, No. 999 Shiguang Road, Yangpu District, Shanghai, 200438, People’s Republic of ChinaEmail wenfangzhuangmed@163.com; tv0801@163.comBackground: Increasing evidences have revealed that solasodine, isolated from Solanum sisymbriifolium fruits, has multiple functions such as anti-oxidant, anti-tumor and anti-infection. However, its role in pancreatic cancer has not been well studied.Methods: To explore the role of solasodine in pancreatic cancer, human pancreatic cell lines including SW1990 and PANC1 were treated with different concentrations of solasodine for 48 h, and cell viability was evaluated by MTT assay, cell invasion and migration were evaluated by Transwell assay. The effect of solasodine on the apoptosis of SW1990 and PANC1 cells was detected by flow cytometry. To further explore the antitumor effect of solasodine in vivo, an SW1990 tumor-bearing mouse model was constructed. The effects of solasodine on cytokines in the serum of SW1990 tumor-bearing mice were also evaluated by ELISA assay.Results: Specifically, in vitro, solasodine could significantly inhibit the proliferation of pancreatic cancer cell lines SW1990 and PANC1 cells. Flow cytometric analysis indicated that solasodine could induce apoptosis of SW1990 and PANC1 cells. Western blot assay indicated that solasodine could significantly inhibit the activation of Cox-2/Akt/GSK3β signal pathway. Meanwhile, the release of Cytochrome c from mitochondria to cytoplasm which can raise the caspases cascade (C-caspase 3 and C-caspase 9) was significantly enhanced by solasodine. In vivo, the results showed that solasodine had potent anti-tumor activities with a lower cytotoxicity. In addition, the serum TNF-α, IL-2 and IFN-γ levels in SW1990 tumor-bearing mice after the treatment of solasodine was significantly increased.Conclusion: Taken together, our results suggested that the solasodine could prevent the progression of pancreatic cancer by inhibiting proliferation and promoting apoptosis, as well as stimulating immunity, suggesting that solasodine might be a potential therapeutic strategy for pancreatic cancer.Keywords: pancreatic cancer, solasodine, Cox-2/Akt/GSK3β signal pathway, apoptosis, apoptosis